Anti-bias education in the early childhood classroom hand in hand, step by step - Kissinger, Katie 1951- (Eye on education books., 2017)
"Anti-Bias Education in the Early Childhood Classroom provides a useful, clearly outlined guide for implementing anti-bias and anti-oppression practices in early childhood education settings. Throughout the book, you'll find: stories from the field; strategies for keeping teaching practices in touch with growing social justice movements; [and] tasks and questions to spark your professional growth in this important area. Katie Kissinger uses her personal experience as a longtime educator to highlight both the challenges and the potential for transformative learning in the anti-bias classroom, and gives other teachers the tools they need to create classrooms that welcome all students and families."--Publisher's description.